What are the thinking styles of Turkish student teachers? - Fer, Seval (TEACHERS COLL OF COLUMBIA UNIV, 2007)
Background: The Thinking Styles Inventory-developed by Sternberg and Wagner based on Sternberg's (1988, 1997) earlier theory of mental self-government-was selected for the research in order to assess thinking styles of student teachers. Another reason is that the theoretical constructs, as well as the inventory generated from the theory, have proved to be valuable to assess thinking styles of people in several studies. For example, previous research reported that students differed in their thinking styles depending on their personal characteristics (e.g., Sternberg & Grigorenko, 1995; Zhang, 1999, 2002b, 2001e). However research found no distinct patterns between thinking styles and personal characteristics of students (e.g., Grigorenko & Sternberg, 1997; Zhang, 2002a). Little research has focused on the study of non-Western students' thinking styles. Thus, it is reasonable to expect that the thinking styles could also be identified among student teachers in Turkey since the styles are differentiated within a different country and culture. Objectives of Study: (1) Mat is the validity and reliability of the Thinking Styles Inventory (TSI) in assessing thinking styles (TS) among Turkish student teachers? (2) Is the structure of a factor analysis of the TSI consistent with the five dimensions postulated by the theory of mental self-government in a Turkish sample? (3) Are TS of student teachers differentiated based on such socialization variables as gender, age, educational level, type of university attended, and field of study followed? Research Design: The study reported here used quantitative methods with a survey sampling design. Subjects: The research subjects were comprised of 402 student teachers enrolled in English, mathematics, and science teaching programs at Yildiz Technical University in Istanbul, Turkey. Results: The results of factor analysis for construct validity of the inventory addressed 13 subscales under the five dimensional constructs with 104 items. Moreover, the total internal reliability of scale was a .92 reliability coefficient. Findings demonstrated that the 13 subscales had internal consistency reliabilities; Cronbach's alphas of the 13 subscales for these subjects ranged from .61 to .91, as well as item-scale correlation that ranged from .37 to .88. Test re-test reliability for external reliability of subscales was between .63 to .78. When the ANOVA findings of the research is evaluated as a whole, it might be said that the student teachers' particular thinking styles were differentiated by the socialized variables of gender age, type of university attended, as well as field of study followed. Conclusions/Recommendations: In order to measure thinking styles of students based on a model of broad intellectual styles, the inventory might be used as an efficient instrument. Moreover, the results of this study demonstrated a diversity of thinking styles among the participants. However, further research is needed to clarify the nature of thinking styles as assessed by the inventory at different educational levels and culture to facilitate a better understanding of the thinking styles of students.
Keywords: MENTAL SELF-GOVERNMENT; ACADEMIC-ACHIEVEMENT; PERFORMANCE; ABILITIES; Education & Educational Research